Hybridization in Metal Wire Additive Manufacturing: A Case Study of an Impeller - Shahu R. Karade; Siddhartha Siddhartha; Neel Kamal Gupta; Ganesan G; K. P. Karunakaran; Henning Zeidler (Metals)
Additive manufacturing (AM) has evolved to enable the direct production of functional components through the hybridization of additive and subtractive processes. In metal wire AM, hybridization is key, encompassing process integration (addition/subtraction), energy source combinations (arc/laser), kinematic options (3/4/5 axis), and slicing techniques (planar/conformal). This paper focuses on these hybridization methods, with a unified system designed for single-machine setups, improving efficiency and accuracy. This study presents a detailed exploration of these hybridization levels through the fabrication of a complex 5-axis geometry—an impeller. The impeller was manufactured with hybridization using various levels and subsequently compared with manufacturing processes like additive manufacturing with interlayer machining and traditional machining methods. The hybrid approach significantly reduced the manufacturing time for the selected impeller geometry from 3536 min to 792 min (saving 77.6% manufacturing time) and minimized material waste to 9.3%, compared with 74.07% in traditional machining. This demonstrates a more efficient, precise, and cost-effective method to optimize metal wire AM for producing complex metal components, advancing capabilities and applications.